"Pus in boots", "Donkey skin", "Hansel and Gretel" canvas signs, tale readings in the digital age - Massol, Jean-François (Ondina - Ondine, 2020)
In addition to offering tales in many forms, particularly animated films, the web presents alsomany teaching sequences offered by teachers on their own behalf or in publishers or institutionalsites. These propositions deserve to be analyzed because they are diverse and do not always refer ina clear way to the genre of the fairy tale or to the different theoretical approaches to it. The study isbased on 26 online sequences and works about Perrault’s tales “The Puss in Boots”, “Donkey Skin”,and the Grimm Brothers “Hansel and Gretel”. Thus, the study of online teaching sequences presentsinterests for the training of students and young professors.Key Words : album of tales , learning sequence , movie , narrative diagram , tale, Web resources.